Mathematical calculation of the occlusal plane and fabrication of complete dentures using the Staub Cranial System - Lampropoulos Panagiotis; Sykaras Nikitas; Türp Jens Christoph (Balkan Stomatological Society, 2024)
Background/Aim: For the fabrication of a removable partial or a complete denture, it is important to reestablish the patient's individual occlusal plane and the vertical dimension of occlusion (VDO). Several methods have been described in the literature to determine the VDO for patients with complete dentures. For this purpose, in the early 1980s, Staub developed a software and a special series of appliances, the so-called Staub Cranial Analysis and Fabrication System for the fabrication of removable dentures as well as for the analysis of casts and existing dentures. The Staub Cranial System is based on defined anatomical reference points on the jaw model. According to Staub, these points should be present on every cast and unchangeable in their position. They are supposed to enable an exact indication of the former position of the natural teeth in a partially or edentulous jaw. Case Report: This paper analyzes the basic principles of Staub Cranial Analysis and presents the clinical application in a clinical case of a fully edentulous patient with initial not satisfactory prostheses. The paper describes in detail the step-by-step analysis process and the artificial teeth arrangement leading to a pleasing and natural set of dentures that anatomically fit in the stomatognathic system of the patient. Conclusions: New diagnostic possibilities, e.g. in orthodontics, prosthetic reconstructions, and implantology, could be implemented using this system. It also could be integrated in digital workflows for complete denture fabrication.